Mechanisms of Adhesion Increase in Wet Sanded Wheel–Rail Contacts—A DEM-Based Analysis - Bettina Suhr; William A. Skipper; Roger Lewis; Klaus Six (Lubricants)
In railways, problems in braking and traction can be caused by so-called low-adhesion conditions. Adhesion is increased by sanding, where sand grains are blasted towards the wheel–rail contact. Despite the successful use of sanding in practice and extensive experimental studies, the physical mechanisms of adhesion increase are poorly understood. This study combines experimental work with a DEM model to aim at a deeper understanding of adhesion increase during sanding. The experimentally observed processes during sanding involve repeated grain breakage, varying sand fragment spread, formation of clusters of crushed sand powders, plastic deformation of the steel surfaces due to the high load applied and shearing of the compressed sand fragments. The developed DEM model includes all these processes. Two types of rail sand are analysed, which differ in adhesion increase in High-Pressure Torsion tests under wet contact conditions. This study shows that higher adhesion is achieved when a larger proportion of the normal load is transferred through sand–steel contacts. This is strongly influenced by the coefficient of friction between sand and steel. Adhesion is higher for larger sand grains, higher sand fragment spread, and higher steel hardness, resulting in less indentation, all leading to larger areas covered by sand.